2019
DOI: 10.1016/j.psychres.2019.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia predicts poorer social and everyday functioning in schizophrenia and bipolar disorder

Abstract: Alexithymia, or the inability to identify and describe one's emotions, is significantly higher in bipolar disorder (BD) and schizophrenia (SZ), compared to healthy controls (HC). Alexithymia has also been observed to predict psychosocial functioning in SZ. We investigated whether alexithymia predicted social and everyday functioning in BD, as well as transdiagnostically in HC, BD, and SZ patients. 56 BD, 45 SZ, and 50 HC were administered and compared on tests measuring neurocognition, social cognition, functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 68 publications
2
20
0
Order By: Relevance
“…Poor emotion awareness has been found to be related to severity of hallucinations, but not delusions, in studies employing retrospective measures, with patients with a lifetime history of more psychotic symptoms displaying poorer emotion awareness 45 . In addition, poor emotion awareness has been found to be a major predictor of social functioning deficits in individuals with schizophrenia 15,46 and at-risk for psychosis 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Poor emotion awareness has been found to be related to severity of hallucinations, but not delusions, in studies employing retrospective measures, with patients with a lifetime history of more psychotic symptoms displaying poorer emotion awareness 45 . In addition, poor emotion awareness has been found to be a major predictor of social functioning deficits in individuals with schizophrenia 15,46 and at-risk for psychosis 17 .…”
Section: Discussionmentioning
confidence: 99%
“…The emotion recognition task (ERT) [ 38 ] is a 7-min test measuring participants’ ability to identify 6 basic facial emotion expressions along a continuum of expression magnitude. Participants fixate on a white “+” cross in the center of the screen for 1500 to 2500 ms, after which a face stimulus is displayed for 200 ms followed by a stimulus mask image for 250 ms.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have identified a relationship between various symptoms of schizophrenia and alexithymia (the inability to identify the meaning and experience of emotion words) (Todarello et al, 2005; Fogley et al, 2014; Ospina et al, 2019) as well as with impaired facial emotion recognition (Tang et al, 2016). Yet, to the best of our knowledge studies examining facial emotion recognition in schizophrenia have rarely assessed the semantic understanding of emotion words prior to facial affect testing (Carra et al, 2017).…”
Section: Introductionmentioning
confidence: 99%